Survival of health workers infected by SARS-CoV-2 in the context of vaccination against COVID-19 in Peru - Escobar-Agreda, Stefan (2021)
Objectives. To evaluate the survival of health personnel infected by SARS-CoV-2 in the context of the vaccination process against COVID-19 in Peru. Methods: A survival analysis was performed using data from national health databases. Data from people between 18 and 59 years old infected with SARS-CoV-2 as evidenced by molecular or antigenic tests were included. Kaplan Meier graphs were produced to compare the survival of health personnel and the rest of the population during 2021 and health personnel during the first and second wave of mortality in Peru in 2020 and 2021, respectively. Results. Data from 998 295 people were included. The average age was 41.2 years (SD 15.8) and 485 167 (48.6%) were women. A higher level of survival of health workers after vaccination was found compared to the general population and to the population of health workers before vaccination. It was evidenced that, at the beginning of the second wave, the risk of dying for health workers was twice that of the first wave (HR = 2). After vaccination (in the sixth month of the second wave), the risk of dying decreased to 87.5% less than in the first wave (HR = 0.125). Conclusions. A positive change has been evidenced in the level of survival of health personnel infected by SARS-CoV-2 during the context of vaccination against COVID-19 in Peru.